Strength and durability characteristics of cement blocks incorporating quarry dust as river sand replacement - Kosalya, S.; Arvinthan, P.; Anburuvel, A.; Sathiparan, N. (University of Ruhuna Sri Lanka, 2021)
In Sri Lanka, due to the recent development in the construction industry, the demand for construction materials is rising quickly. River sand is primarily used for civil engineering constructions and especially for masonry house unit construction. The over-exploitation of river sand to encounter the demand has led to various harmful consequences. Considering the environmental issue due to the scarcity of sand, there are several alternative materials consider as river sand replacements in masonry block production. Quarry dust is one of such materials consider as river sand alternative due to its beneficial characteristic such as better contribution to the strength of the cementitious material, better workability, lesser cement consumption and eco-friendly. In the present study, the quarry dust replacement levels of 0, 33, 66, and 100 % of river sand are used for cement block production. The compressive strength, water absorption, sorption, and wet and dry resistance were tested for cement blocks after 28 days of curing. Test results show that, cement blocks with quarry shown better strength and durability characteristics.
Keywords: Masonry; River sand; Quarry dust; Cement blocks; Compressive strength; Durability